EFEKTIVITAS PROGRAM BANTUAN RUMAH TIDAK LAYAK HUNI (RUTILAHU) DI DINAS PERUMAHAN RAKYAT DAN KAWASAN PERMUKIMAN (PRKP) KABUPATEN KARAWANG (Studi Kasus Pelaksanaan Rutilahu di Kecamatan Karawang Barat) - Nunu Nurdiana Priyatna; Hanny Purnamasari; Rachmat Ramdani (Universitas Indo Global Mandiri, 2022)
ABSTRACT The Rehabilitation Program of Uninhabitable Houses (Rutilahu) is a program of the Karawang Regency Public Housing and Residential Area Office (DPRKP) to increase the number of habitable homes in Karawang Regency aimed at poor households in Karawang Regency, especially those with uninhabitable homes and adequate health sanitation. Rutilahu program implemented in 2016 to 2019 has renovated 5,711 houses in Karawang Regency. This research aims to find out how effective the implementation of the Rutilahu Program by the Karawang Regency PRKP Office (case study in Mekarjati village of West Karawang Subdistrict). The methods used in this study are descriptive with a qualitative approach. The data collection techniques that researchers conduct using interviews, observations and documentation. Actions in data analysis are data reduction, data presentation, conclusion withdrawal and verification and using the effectiveness theory of Ni Wayan Budiani which includes the accuracy of program goals, program socialization, program objectives and program monitoring. The results of this study can be known that the effective implementation of the Rutilahu Program by the Karawang Regency PRKP Office (case study in Mekarjati village of West Karawang District) in Karawang Regency has been going quite well. But based on research in the field there are still problems that need to be addressed to improve the results of the Rutilahu program. The advice that researchers can give is to the implementers of the Rutilahu Program to further maximize the implementation of the Rutilahu Program in terms of program goals and program socialization. So that the public can receive information and benefits of the program clearly.Keywords: Effectiveness, Program, Rutilahu